Perkembangan Konsep Kedaulatan Negara dalam Hukum Laut Internasional Pasca Berlakunya BBNJ Agreement 2023 dan Advisory Opinion ICJ 2025 - NURUL 'ASYIQIN (Jurnal Hukum Lex Generalis, 2026)
Developments in international law of the sea following the 2025 ICJ Advisory Opinion, the 2024 ITLOS Advisory Opinion and the 2023 BBNJ Agreement have prompted a fundamental shift in the concept of state sovereignty. This study examines the transformation of sovereignty in international law of the sea and its implications for Indonesia. Using a normative legal research method with treaty, conceptual and case approaches, the study finds that sovereignty is no longer understood as an exclusive right to exploit marine resources, but rather as a responsibility to protect the global environment through the implementation of stringent due diligence obligations, erga omnes commitments and collective governance mechanisms for areas beyond national jurisdiction. These developments necessitate the harmonization of Indonesia’s domestic legal framework following the ratification of the BBNJ Agreement through Presidential Regulation No. 67 of 2025.